2013
DOI: 10.1111/bjhp.12063
|View full text |Cite
|
Sign up to set email alerts
|

Predicting quality of life 5 years after medical discharge for traumatic spinal cord injury

Abstract: What is already known on this subject? Life satisfaction and self-rated health status are important aspects of quality of life following traumatic spinal cord injury. Functional impairment has been inconsistently predictive of these variables over time. Prospective research to date has not examined the mediating effects of participation in predicting quality of life. What does this study add? The results indicate that greater functional impairment and pain are prospectively predictive of lower participation. G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 40 publications
4
47
1
1
Order By: Relevance
“…Erosa, et al, by contrast found that people with spinal cord injury for whom severe functional disorders have been defined do not always evaluate their overall health status as being bad. Better participation in society is experienced by those respondents who have a better evaluation of their physical functioning (getting around, self-care, and life activities), and that corresponds to studies about the evaluation of quality of life and physical functioning [9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…Erosa, et al, by contrast found that people with spinal cord injury for whom severe functional disorders have been defined do not always evaluate their overall health status as being bad. Better participation in society is experienced by those respondents who have a better evaluation of their physical functioning (getting around, self-care, and life activities), and that corresponds to studies about the evaluation of quality of life and physical functioning [9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…This resulted in a final sample of 16 independent studies. 11,18,24,26,[29][30][31][32][33][34][35][36][37][38][39][40] Data extraction and organisation…”
Section: Psychosocial Aspects Of Sci Pain J Tran Et Almentioning
confidence: 99%
“…8,9 For example, Donnelly and Eng 17 found that pain intensity was significantly associated with one's ability to reintegrate into the community in the first 6 months post SCI. Longitudinal studies have also demonstrated that those with pain report less social interaction and support compared with pain-free peers, 18 and lower satisfaction with their participation in daily self-care activities, family roles and relationships. 19 Notably, these studies have operationalised participation in various ways, highlighting the multidimensionality of this concept.…”
Section: Introductionmentioning
confidence: 99%
“…The present study also showed that women exhibited a lower degree of accessibility in the physical and social environment compared to men. Other studies reported that married people with SCI have less depression, greater psychological well-being and better QoL [23,24], due to the improved social participation that the status of marriage provides [25]. In the present series, the marital status partially affects social reintegration; married people with SCI have less cognitive independence and transfers ability.…”
Section: Discussionmentioning
confidence: 44%
“…Gender and marital status should probably be considered important factors for SR and QoL of patients with SCI [3,12,13,[22][23][24][25]. Most studies reported that women with SCI exhibit a lack of vitality and vigor [12], and have a higher proportion of medical, social and psychological problems [13], which explains their decreased participation in educational, voluntary and recreational activities [3].…”
Section: Discussionmentioning
confidence: 99%